1996
DOI: 10.1523/jneurosci.16-13-04250.1996
|View full text |Cite
|
Sign up to set email alerts
|

Kainic Acid-Induced Seizures Enhance Dentate Gyrus Inhibition by Downregulation of GABABReceptors

Abstract: Seizures cause a persistent enhancement in dentate synaptic inhibition concurrent with, and possibly compensatory for, seizure-induced hippocampal hyperexcitability. To study this phenomenon, we evoked status epilepticus in rats with systemic kainic acid (K A), and 2 weeks later assessed granule cell inhibition with paired-pulse stimulation of the perforant path (PP) in vitro. Controls demonstrated three components of paired-pulse inhibition: early inhibition (10 -30 msec), intermediate facilitation (30 -120 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 67 publications
9
64
1
Order By: Relevance
“…Thus, the selective loss of inhibitory input to the GCL has been suggested to enhance hippocampal excitability. However, it should also be noted that a number of studies have found that inhibitory drive to the GCL is enhanced in animal models of TLE (Tuff et al, 1983;Haas et al, 1996;Buckmaster and Dudek, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the selective loss of inhibitory input to the GCL has been suggested to enhance hippocampal excitability. However, it should also be noted that a number of studies have found that inhibitory drive to the GCL is enhanced in animal models of TLE (Tuff et al, 1983;Haas et al, 1996;Buckmaster and Dudek, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We further asked whether postnatal LPS treatment could generate a comparable susceptibility to a different chemoconvulsant that also causes a well defined pattern of neuronal damage in the hippocampus, yet through an entirely different mechanism of action as LI-PILO and PTZ. Male rats received either saline or LPS (100 g/kg) on P14 as described above (n ϭ 6 -7/group), and then 2 months later received 15 mg/kg KA intraperitoneally (Haas et al, 1996). Seizure onset time was recorded as defined above for LI-PILO, and pentobarbital (20 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Interstimulus intervals between the paired stimuli ranged from 10 to 1000 ms, corresponding to frequencies of 100 to 1 Hz. The paired stimuli were repeatedly applied to the same tissue every 30 s. This interval ensured full recovery between stimuli so that the response to one stimulus pair was not affected by the previous stimulus pair (Haas et al, 1996). Extracellular evoked responses (population spikes) were recorded using glass recording micropipette (1-5 M⍀) filled with 2 M NaCl placed in the middle third of the external blade of the dentate gyrus granule cell layer (stratum granulosum).…”
Section: Methodsmentioning
confidence: 99%
“…The paired-pulse curve was constructed by calculating population spike amplitude ratio (R 2 /R 1 ) at increasing interstimulus intervals. The curve consisted of three components (Haas et al, 1996;Velíšek and Velíšková, 2002) referred to here as (1) early inhibition (10 -50 ms), (2) intermediate facilitation (70 -125 ms), and (3) late inhibition (150 -1000 ms). Slices from OVX females treated with four daily doses of ␤-estradiol (2 g/rat; n ϭ 22) displayed significant enhancement of late paired-pulse inhibition at interstimulus intervals 125-1000 ms compared with slices from OVX controls (n ϭ 22) receiving oil (two-way ANOVA; main effect of treatment, F (1,42) ϭ 15.871; *p Ͻ 0.001).…”
Section: ␤-Estradiol Increases Npy Expression Within the Hilar Internmentioning
confidence: 99%